Video Post Production for Low-Budget Films. - Angel, Eduardo (linkedin.com, 2016)
Get tried-and-true post-production tips for low-budget or ultra-low-budget video projects. Learn effective post-production techniques from Emmy-winning filmmaker Eduardo Angel.